Proteomics insights: proteins related to larval attachment and metamorphosis of marine invertebrates - Chandramouli, Kondethimmanahalli H.; Qian, Pei-Yuan; Ravasi, Timothy (Frontiers in Marine Science, 2014)
The transition in an animal from a pelagic larval stage to a sessile benthic juvenile typically requires major morphological and behavioral changes. Larval competency, attachment and initiation of metamorphosis are thought to be regulated by intrinsic chemical signals and specific sets of proteins. However, the molecular mechanisms that regulate larval attachment and metamorphosis in marine invertebrates have yet to be fully elucidated. Despite the many challenges associated with analysis of the larvae proteome, recent proteomic technologies have been used to address specific questions in larval developmental biology. These and other molecular studies have generated substantial amount of information of the proteins and molecular pathways involved in larval attachment and metamorphosis. Furthermore, the results of these studies have shown that systematic changes in protein expression patterns and post-translational modifications (PTM) are crucial for the transition from larva to juvenile. The degeneration of larval tissues is mediated by protein degradation, while the development of juvenile organs may require PTM. In terms of application, the identified proteins may serve as targets for antifouling compounds, and biomarkers for environmental stressors. In this review we highlight the strengths and limitations of proteomic tools in the context of the study of marine invertebrate larval biology.